2021
DOI: 10.1186/s12263-020-00681-1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal folic acid impacts DNA methylation profile in male rat offspring implicated in neurodevelopment and learning/memory abilities

Abstract: Background Periconceptional folic acid (FA) supplementation not only reduces the incidence of neural tube defects, but also improves cognitive performances in offspring. However, the genes or pathways that are epigenetically regulated by FA in neurodevelopment were rarely reported. Methods To elucidate the underlying mechanism, the effect of FA on the methylation profiles in brain tissue of male rat offspring was assessed by methylated DNA immunopr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 56 publications
3
7
0
Order By: Relevance
“…[ 25–29 ] Recently, many researchers pointed that prenatal malnutrition was closely linked with development of multiple organs via different mechanisms in offspring. [ 30–33 ] In the present study, we first validated that prenatal high‐sucrose diet increased maternal weight before delivery, but it had no effect on the fetal number. Consistent with a population‐based cohort study with 40 years of follow‐up investigated that prenatal hyperglycemia increased rates of early onset cardiovascular diseases from childhood to early adulthood, [ 34 ] our previous data confirmed that prenatal high sucrose impaired the micro‐vascular function of adult and aged offspring.…”
Section: Discussionsupporting
confidence: 51%
“…[ 25–29 ] Recently, many researchers pointed that prenatal malnutrition was closely linked with development of multiple organs via different mechanisms in offspring. [ 30–33 ] In the present study, we first validated that prenatal high‐sucrose diet increased maternal weight before delivery, but it had no effect on the fetal number. Consistent with a population‐based cohort study with 40 years of follow‐up investigated that prenatal hyperglycemia increased rates of early onset cardiovascular diseases from childhood to early adulthood, [ 34 ] our previous data confirmed that prenatal high sucrose impaired the micro‐vascular function of adult and aged offspring.…”
Section: Discussionsupporting
confidence: 51%
“…Based on the above analysis, it can be concluded that HAR1A take an important role in neuroactive ligand-receptor, synaptic and axon guidance. Those are all critical processes in the early development of the brain (33). Neurons migrate to proper locations to make connections by emitting axons during the development of the brain (34).…”
Section: Discussionmentioning
confidence: 99%
“…It is known from animal studies that folic acid supplementation impacts DNA methylation implicated in neurodevelopment and learning/memory abilities [77]. In this review, evidence of the benefit of folic acid supplement use, and the timing at which supplementation was initiated, on foetal brain development was inconsistent.…”
Section: Folic Acid Supplement Usementioning
confidence: 99%